Influência da avaliação dos consumidores sobre propaganda nas dimensões do valor da marca - Streb, Cássia Tavares (2018)
Marketing professionals seek to create unique identities for their brands (NIADA and BAPTISTA, 2013), and for this reason, brands have been widely discussed in the literature and have received special interest and attention in the business environment (GONÇALVES FILHO, SANTOS JÚNIOR and SOUKI, 2017), and the study of brand equity (Brand Equity) is one of the topics that has been growing and gaining importance in this area since the brand is used to identify the manufacturer of the product, differentiate it from other offers and to add value, contributing to the achievement of competitive advantage (CAPUTO, MACEDO and NOGUEIRA, 2008; GONÇALVES FILHO et al., 2009). The researchers recognize the value of brand as an indicator of performance, source of competitive advantage and component of business success (CHRISTODOULIDES, CADOGAN and VELOUTSOU, 2015; CHATZIPANAGIOTOU, VELOUTSOU and CHRISTODOULIDES, 2016), since the consumer is able to recognize the product previously consumed and approved, this is a sign that there is an advantage over the others (GONÇALVES FILHO et al., 2017). While brand value can be derived from various stakeholders, its consumer-based study (CBBE) dominates marketing research. However, it is still difficult to grasp the full complexity of the issue, which highlights the need for more holistic, advanced CBBE models that provide additional information on the creation of brand equity (DAVCIK, SILVA and HAIR, 2015; CHATZIPANAGIOTOU et al., 2016). The present research aims to verify the influence of investments in advertising on the dimensions of the brand value of Brazilian broadband service providers. To reach this objective, the survey method was adopted through a structured questionnaire through personal interviews with consumers of the fixed broadband service of the cities of Porto Alegre - RS and Florianópolis - SC. The collection instrument is based on works by several authors, the main ones being Oliveira, Silveira and Luce (2015), Buil, Chernatony and Martinez (2008) and Yoo, Donthu and Lee (2000). For the analysis of the data, a verification was first made regarding lost data and atypical observations, being the database submitted to treatments that allowed the inference of Normality, Linearity and Multicollinearity assumptions. The main statistical tests used were descriptive statistical tests (mean, fashion, standard deviation), analysis of variance (ANOVA), exploratory factorial analysis (AFE) and modeling of structural equations (MEE). The main results show that the Brand Consciousness, Brand Associations, Perceived Quality and Brand Loyalty dimensions make up the Overall Brand Value with the percentages 74%, 97%, 86%, and 98%, respectively. Advertising also influences the dimensions of brand value with the percentages 38% (Brand Awareness), 9% (Brand Associations), 11% (Perceived Quality) and 8% (Brand Loyalty). For future research it is indicated that other antecedents and / or other dimensions of the brand's value are used, and also that the study is carried out with another service or product sector. Also, it is indicated that the instrument of data collection is applied in other cultures, and it is possible that it is replicated in other countries.